2016
DOI: 10.22208/jdmfs.1.1.2016.35-38
|View full text |Cite
|
Sign up to set email alerts
|

Concentration of total protein and degree of acidity (pH) of saliva when fasting and after breakfasting

Abstract: Background: While fasting, the mouth does not work to eat and drink so that the salivary glands become less active so saliva production decreased and there was a change in eating timewhich is relation to the mastication process that impact on changes in the degree of acidity (pH) Objectives: To determine the concentration of total protein and the degree of acidity (pH) of saliva when fasting and after breakfasting. Materials and Methods: The study was observational analytic design with longitudinal (follow up … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 3 publications
0
3
0
2
Order By: Relevance
“…Hal ini sesuai dengan penelitian Gemiani dkk (2018) dan penelitian Illahi dkk (2016) yang menunjukkan adanya penurunan pH plak pada kelompok kontrol tanpa diberikan perlakuan dan rata-rata pH saliva yang menjadi lebih rendah pada saat puasa. 17,18 Penurunan pH plak dapat dikaitkan dengan akumulasi plak yang terjadi dalam 1 jam setelah dilakukan profilaksis oral. Pembentukan plak dimulai 1 menit setelah gigi dibersihkan.…”
Section: Pembahasanunclassified
See 1 more Smart Citation
“…Hal ini sesuai dengan penelitian Gemiani dkk (2018) dan penelitian Illahi dkk (2016) yang menunjukkan adanya penurunan pH plak pada kelompok kontrol tanpa diberikan perlakuan dan rata-rata pH saliva yang menjadi lebih rendah pada saat puasa. 17,18 Penurunan pH plak dapat dikaitkan dengan akumulasi plak yang terjadi dalam 1 jam setelah dilakukan profilaksis oral. Pembentukan plak dimulai 1 menit setelah gigi dibersihkan.…”
Section: Pembahasanunclassified
“…Hal ini menyebabkan kelenjar saliva menjadi kurang aktif dan produksi saliva menjadi berkurang, sehingga terjadi penurunan pada pH saliva. 18 Hasil penelitian menunjukkan aplikasi Difluorosilane 0,9% menghasilkan perubahan pH plak yang lebih rendah dibandingkan aplikasi kombinasi Sodium fluoride 5% dengan Tricalcium phosphate. Hal ini kemungkinan berhubungan dengan konsentrasi fluoride dalam plak.…”
Section: Pembahasanunclassified
“…The role of saliva is not only for the mastication process but also to protect the tissue inside the oral cavity. 5,6 In normal circumstances, salivary pH is about 6.8 to 7.2 but some types of carbohydrates are converted by bacteria and result in a decreased pH of the saliva. 7 Natural ingredients from plants in Indonesia can be used to inhibit this process.…”
Section: Introductionmentioning
confidence: 99%
“…Its production and secretion is affected by stimulation, diet, fasting, age, sex, and medications. 2,3 Saliva analysis can determine one's body condition due to substances movement from blood to saliva through several mechanisms, such as passive diffusion, active transport, and ultrafiltration (gap junction). 4,5 Previous studies found that saliva analysis can determine Cystic Fibrosis, Sjogren's Syndrome, Squamous Cell Carcinoma, periodontal disease, stress, acute myocardial infarct, cholesterol, pancreatic cancer, and the disability to absorb Calcium.…”
Section: Introductionmentioning
confidence: 99%